Modern Activity Styles of Teachers - Turayeva Dilafruz Rustamboevna (International Journal on Integrated Education, 2022)
The article presents the results of a study of the styles of activity of teachers of professional colleges. The data of factor analysis between the indicators of the used research methods are presented and the identified 8 styles of activity typical for teachers of professional colleges are described.